A modified version of the interlocking finger test as a bedside screening test for visuospatial deficits and dementia in Parkinson's disease. Issue 4 (7th March 2022) - Schmidt, Nele; Strohmaier, Tim; Witt, Karsten
Abstract: Introduction: Objective of this study was to examine if the Interlocking Finger Test (ILFT) is a suitable bedside screening test for visuospatial functions and/or dementia in Parkinson's disease (PD) patients aiming to facilitate the diagnosis of a dementia syndrome associated with posterior cortical and temporal lobe dysfunction according to the dual syndrome hypothesis (frontostriatal vs. posterior cortical cognitive impairment). Methods: Forty‐seven PD patients were assessed with the ILFT and an extensive cognitive test battery. The ILFT was carried out in the original version as well as in three modified versions of the test including a fifth figure and/or a more complex rating system, leading to four different ILFT scores (named after the maximum achievable scoring result: ILFT 4, ILFT 5, ILFT 12, and ILFT 15). We conducted a correlation analysis to reveal associations between the ILFT scores and cognitive as well as motor impairments. Receiver operating curve (ROC) analyses were calculated to evaluate the ability of the ILFT scores to predict visuospatial impairments and dementia. Results: ILFT scores correlated significantly with global cognition, visuospatial functions, memory, attention, and age ( p < .0125) but not with executive functions, language, education, depression, and motor impairment. The ROC analyses revealed ILFT 15 as best predictor for visuospatial deficits and dementia with an area under the curve of .82 and .88, respectively. Conclusion: The ILFT is suitable for detecting symptoms of the posterior cortical degeneration syndrome according to the dual syndrome hypothesis. We recommend the use of the modified test version ILFT 15. Abstract : The dual syndrome hypothesis differentiates between dopamine modulated frontal‐striatal network dysfunction and a dementia syndrome associated with more posterior cortical degeneration and prodromal visuospatial deficits in Parkinson's disease. In this study, we showed that the Interlocking Finger Test is a suitable bedside screening test for the diagnosis of the posterior cortical degeneration syndrome.